2015
DOI: 10.1093/jxb/erv093
|View full text |Cite
|
Sign up to set email alerts
|

Winter cold-tolerance thresholds in field-grownMiscanthushybrid rhizomes

Abstract: Highlight: LT50 values in diploid rhizomes of Miscanthus indicated that they retain mechanisms that confer higher tolerance of lower temperatures than occurs in the more-productive polyploid lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…In the case of genotypes 2603, C124 and C148, the increased REL was statistically insignificant. Many studies use 50% electrolyte leakage as the critical viability threshold, although many plants perish after suffering more than 30% electrolyte leakage (Peixoto et al 2015). Comparing the individual genotypes, obviously, the highest values of REL were measured in stressed plants immediately after the effect of the freezing temperature -3°C (S1) in the C98 genotype (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of genotypes 2603, C124 and C148, the increased REL was statistically insignificant. Many studies use 50% electrolyte leakage as the critical viability threshold, although many plants perish after suffering more than 30% electrolyte leakage (Peixoto et al 2015). Comparing the individual genotypes, obviously, the highest values of REL were measured in stressed plants immediately after the effect of the freezing temperature -3°C (S1) in the C98 genotype (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous controlled-environment studies have estimated the temperature at which 50% of isolated M×g '1993-1780' rhizomes are killed (LT 50 ) as ranging from −2.6°C to −4.4°C Fonteyne et al, 2016;Peixoto, Friesen, & Sage, 2015), which might have led one to predict lower survival rates at the Urbana and Dixon Springs locations than was observed based on the minimum temperatures at 10 cm below bare soil for each site (−6.2 and −5.3°C at Urbana and Dixon Springs, respectively). However, this apparent discrepancy between results from the laboratory and the field could be accounted for by the insulation of belowground rhizomes from the plant's aboveground crown, and/or avoidance of cold by rhizomes that grew deep in the soil (i.e., more than 10 cm belowground).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the survival of mature M×g ‘1993‐1780’ plants in this study, in a parallel study of first year M×g ‘1993‐1780’ plants, we observed losses of 29% during the 2013–2014 winter at Urbana, IL (Dong, Green, et al, ). Previous studies have estimated the temperature at which 50% of isolated rhizomes from mature plants were killed (LT 50 ) for M×g ‘1993‐1780’ to be −2.6°C (Fonteyne et al, ), −3.4°C (Clifton‐Brown & Lewandowski, ), or −4.4°C (Peixoto et al, ), but in the field, insulation of belowground rhizomes from the plant’s aboveground crown, and avoidance of cold by rhizomes that grow deep in the soil, can increase overwintering ability of mature plants. For example, under sod, the minimum temperature during the 2013–2014 winter at Urbana was only‐2.2°C at 10 cm and −1.4°C at 20 cm.…”
Section: Discussionmentioning
confidence: 99%